PENGARUH PENERAPAN MODEL PEMBELAJARAN MARKET PLACE ACTICITY TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS VIII - Al- Qanit Qurba; Abdi Yusra; Aprizal Ahmad; Serpuadi Zeky; Azvi Rahmi; Fatimah Fatimah (Jurnal Manajemen Pendidikan, 2026)
This study aimed to analyze the effect of implementing the Market Place Activity learning model on students' learning outcomes in Islamic Religious Education among eighth-grade students at SMP Negeri 38 Padang. Methods: The study employed a quantitative approach using a survey method. The population consisted of 203 eighth-grade students in the 2021/2022 academic year, while a sample of 40 students was selected through simple random sampling. Data were collected using questionnaires and documentation, and were analyzed using descriptive statistics and an independent t-test. Results: The findings indicated that the implementation of the Market Place Activity learning model was categorized as moderate, with a percentage of 67.5%. Similarly, students' learning outcomes were also classified as moderate, with a percentage of 55%. The hypothesis testing revealed a significance value of 0.000 (< 0.05), with a calculated t-value of 5.656, which was greater than the critical t-value of 1.686. These results indicate a statistically significant effect of the Market Place Activity learning model on students' learning outcomes. Implications: The implementation of the Market Place Activity learning model can serve as an effective alternative learning approach to improve pupils’ learning outcomes.